Spectroscopic and Radiative Properties of Several Nd3+ Ions in Borate Glass System - Juniastel Rajagukguk; M. Djamal; R. Hidayat; Suprijadi Suprijadi; A. Aminudin; J. Kaewkhao (Chemistry Department, The University of Brawijaya, 2016)
Radiative properties and spectroscopic studies of several Nd3+ doped Borate glass system have been reported. Judd-Ofelt intensity parameter and other parameters like oscillator strength (f), effective bandwidth (Dleff), radiative transition probabilities (AR), stimulated emission cross section (s), branching ratio (bR), radiative lifetime (tR) and experimental lifetime (texp) for the hypersensitive Nd3+ doped Borate Glass are listed and discussed. The variation of W2 values for the different host matrix are expressed their covalency among Nd3+ ions in the glass matrix. In this study, reported that the hypersensitive transition achieved at 4I9/2 ® 4G5/2, 2G7/2 centered at 580 – 585 nm range.